I DoN't SLeep iN a Tree! : I SLeep iN a... - Durant, Alan; Hinton, Steph (Bath, England : Bookoli Ltd., 2019)
This sweet story introduces children to the concept of mindfulness, providing everyday situations to help them identify opportunities to be mindful. Beautiful illustrations by Sarah Ward bring these characters to life and frame the stories in a way kids will relate to.
Keywords: Picture books for children; Illustrated books, Children's.